2010
DOI: 10.1111/j.1750-3639.2010.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Pathophysiology: Insights Emerging from Proteomics

Abstract: Proteomics is increasingly employed in both neurological and oncological research to provide insight into the molecular basis of disease but rarely has a coherent, novel pathophysiological insight emerged. Gliomas account for >50% of adult primary intracranial tumors, with malignant gliomas (anaplastic astrocytomas and glioblastoma multiforme) being the most common. In glioma, the application of proteomic technology has identified altered protein expression but without consistency of these alterations or their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 83 publications
(128 reference statements)
4
75
0
1
Order By: Relevance
“…Many of the differentially expressed proteins identified in this study have been previously reported in GBM biomarker studies using other proteomic methods including 2-DE, 2D-DIGE, and other MS-based techniques (12,31,46). In addition, we identified several new proteins that were not reported before in the context of GBM (Supplementary Table S1).…”
Section: Discussionsupporting
confidence: 73%
“…Many of the differentially expressed proteins identified in this study have been previously reported in GBM biomarker studies using other proteomic methods including 2-DE, 2D-DIGE, and other MS-based techniques (12,31,46). In addition, we identified several new proteins that were not reported before in the context of GBM (Supplementary Table S1).…”
Section: Discussionsupporting
confidence: 73%
“…Several proteomic studies have also been reported providing important insights in the pathophysiology of these tumors (1,9). In our previous study, we compared whole tissue extracts from various grades of glioma with control specimens employing a two-dimensional electrophoresis-MS approach and identified 72 differentially expressed proteins, of which 27 were present in multiple tumor specimens (10).…”
mentioning
confidence: 99%
“…The increased TROY expression was strongly inversely related with the life span of patients (44). Meanwhile, RhoGDI␣ was found to be down-regulated in glioma cells (41,46). Furthermore, the increased TROY expression and decreased RhoGDI␣ expression were accompanied with reduced RhoA activation and increased Rac1 activation in glioma cells (44,(47)(48)(49).…”
Section: Discussionmentioning
confidence: 93%